2014
DOI: 10.1186/1744-8069-10-52
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Phosphatidic Acid Relieves Osteoarthritis Symptoms

Abstract: BackgroundCyclic phosphatidic acid (cPA) is a naturally occurring phospholipid mediator with a unique cyclic phosphate ring at the sn-2 and sn-3 positions of its glycerol backbone. Natural cPA and its chemically stabilized cPA derivative, 2-carba-cPA (2ccPA), inhibit chronic and acute inflammation, and 2ccPA attenuates neuropathic pain. Osteoarthritis (OA) is a degenerative disease frequently associated with symptoms such as inflammation and joint pain. Because 2ccPA has obvious antinociceptive activity, we hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…Cell culture was performed as previously described ( 25 ). Human chondrogenic SW1353 cells (American Type Culture Collection, Manassas, VA, USA) were cultured in Dulbecco's modified Eagle's medium (DMEM; Thermo Fisher Scientific, Inc., Waltham, MA, USA) containing 10% fetal bovine serum (HyClone; GE Healthcare Life Sciences, Logan, UT, USA) supplemented with streptomycin (100 µg/ml) and penicillin (100 U/ml; both Thermo Fisher Scientific, Inc.) in 25 cm 2 culture flasks at 37°C in a humidified atmosphere with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture was performed as previously described ( 25 ). Human chondrogenic SW1353 cells (American Type Culture Collection, Manassas, VA, USA) were cultured in Dulbecco's modified Eagle's medium (DMEM; Thermo Fisher Scientific, Inc., Waltham, MA, USA) containing 10% fetal bovine serum (HyClone; GE Healthcare Life Sciences, Logan, UT, USA) supplemented with streptomycin (100 µg/ml) and penicillin (100 U/ml; both Thermo Fisher Scientific, Inc.) in 25 cm 2 culture flasks at 37°C in a humidified atmosphere with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Considering the breadth of bioactivities of this class of lipids [ 47 ], their contributions to immune responses may be diverse, particularly since they modulate nuclear function [ 48 , 49 ]. In this regard, pharmacological studies have shown that cPA analogs potently reverse experimental osteoarthritis [ 50 ], block immune-induced demyelination [ 51 ], and inhibit the growth of cancer cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…For cartilage explant culture, full-thickness cartilage tissue was cut into pieces of 5 mm. Following 48 hrs of culture in Dulbecco's modified Eagle's medium/F-12 containing 10% foetal bovine serum and 50 units/ml of penicillin and streptomycin, the explants were treated with IL-1b (10 ng/ml) (PeproTech), ANE (10 lM) and ibuprofen (10 lM) (Sigma-Aldrich) for 4 days under serum-free conditions with ITS (insulin-transferrin-selenium; Sigma-Aldrich) according to previous studies [20][21][22][23]. Following 4-day culture, the medium was collected and the explants were fixed in 4% paraformaldehyde.…”
Section: Human Articular Cartilage Explant Culturementioning
confidence: 99%